SEROPREVALENCIA DEL VIRUS DE LA RINOTRAQUEITIS INFECCIOSA BOVINA EN GANADO LECHERO DEL VALLE DE LIMA - Sánchez T., Gabriela (2003)
The seroprevalence of bovine herpes virus type 1 (BHV-1), the causative agent of Infectious Bovine Rhinotracheitis (IBR) was determined in non-vaccinated bovines older than 6 months of age and reared in 12 dairy farms in the valley of Lima, Peru. Blood samples were collected from 395 animals and assayed for antibodies to BHV-1 by using virus neutralization test. Antibodies against BHV-1 were detected in 26 ± 0.47% (143/395) of the animals with titers between 2 and >256. Sixty seven per cent (8/12) of herds had seropositive animals. The higher prevalence was found in herds with more than 300 animals and in herds located in the north and south of Lima, and in those animals older than 2 years. These results confirmed the wide distribution of BHV-1 in the Lima valley, despite of the absence of clinical signs. Since farmers have indicated to have observed respiratory diseases in young animals, the BHV-1 would be associated to the bovine respiratory complex in calves.